Doing business with Japan - Tanaka, H. William (Business book international, 1986)
Doing Business in Japan Anyone who has ever spent time doing business in Japan will tell you that it is a land of contrasts; technologically innovative and modern yet traditional and hierarchical. Japan boasts excellence in sectors as wide-ranging as finance, automotive, computing and pharmaceuticals and is viewed as a major global influence – even despite the recent economic rise of China and India. The county is deemed as ‘mostly free’ in terms of economic freedom, with businesses able to operate without the hindrance of excessive government controls. The nation also scores highly on the World Bank’s scale for ranking business ease.